A study on the toxic effects of tobacco dust on brackishwater fishpond snail, Cirrithidia sp. - Prieto, Lourfame Decolongon (1979.)
Short term static bioassay test on the toxic effects of tobacco dust on brackishwater fishpond snails, Cirrithidia sp. was conducted for a duration of 96 hours under laboratory conditions. Four treatments in three replicates were utilized (0 ppm, 20 ppm and 40 ppm) and arranged in a complete random block design. Mortality was recorded every after 24 hours for a period of 96 hours. Greatest mortality occured at the highest concentration of 40 ppm. Sublethal concentration of the toxicant was determined by graphical interpolation on a semi-logarithmic paper in terms of median tolerance limit (TL m50). TL50 values were determined at 72 and 96 hours of exposure, and was calculated at 34 ppm and 22 ppm respectively. (NOTE CORRECTION: m50 TL50).
Research Paper (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Snails; Brackishwater Fishpond